When language becomes law - Chiocchetti, Elena (Linguistica (Ljubljana), 2013)
South Tyrol is a part of Northern Italy where a large German-speaking minority lives. In 1972 the local population was granted the right to use the minority language with the public administration, in court and in all realms of public life (DPR 672/1972). An urgent need for a clear and consistent German legal language that faithfully reflected the Italian legal system ensued. The task of responding to such terminological emergency was assigned to a commission of six legal experts and translators (DPR574/1988), who were to officially validate (i.e. standardise) the German language equivalents to the existing legal and administrative Italian terms. The use of the newly standardised terminology is mandatory for all public bodies. After about 20 years of activity, the proposed paper aims at analysing the results obtained and difficulties faced by the Commission during their daunting task of creating a German language terminology to express the concepts of Italian law with a constant view to the neighbouring well-established German speaking legal systems. The paper will illustrate the decision-making process, term selection criteria and strategies of neologyas well as discuss the procedural problems and terminological inconsistencies on the basis of real examples.
Keywords: allemand; droits linguistiques; German; Italian; italien; italijanščina; jezikovne pravice; Južna Tirolska; law; nemščina; pravna terminologija; pravo; standardisation terminologique; terminologie juridique; Tyrol du Sud